Ethics in the light of a naturalistic and religious interpretation of the world - Wojewoda, Mariusz (Folia Philosophica, 2007)
The article shows tension which exists at the contact of two models devoted to an interpretation of the world, i.e. a religious and naturalistic one. The author discusses: J. Hick, R. Braithwaite, A. MacIntyre, defends a religious understanding of reality, basing on the achievements of contemporary philosophy and methodological tools worked out by it. The philosophy of religion based on pluralistic assumptions does not consist in the undermining of this naturalism at all, but criticism of reductionistic tendencies connected with it. A naturalistic view on the world, which was developed at the end of the 19th century, led to the undermining of the legitimacy of religious convictions. Their defence from anthropological positions is connected with a postulate of an adequate and dialogic way of understanding man. In a multicultural dialogue, which is an intellectual call of our times, one should not escape the aspect of religion. Philosophy can help in developing the language to enable this dialogue.